Addressing Reduced Laboratory-Based Pulmonary Function Testing During a Pandemic (2020)
To reduce the spread of SARS-CoV-2, many pulmonary function testing (PFT) laboratories have been closed or have significantly reduced their testing capacity. Because these mitigation strategies may be necessary for the next 6 to 18 months to prevent recurrent peaks in disease prevalence, fewer objective measurements of lung function will alter the diagnosis and care of patients with chronic respiratory diseases. PFT, which includes spirometry, lung volume, and diffusion capacity measurement, is essential to the diagnosis and management of patients with asthma, COPD, and other chronic lung conditions. Both traditional and innovative alternatives to conventional testing must now be explored. These may include peak expiratory flow devices, electronic portable spirometers, portable exhaled nitric oxide measurement, airwave oscillometry devices, and novel digital health tools such as smartphone microphone spirometers and mobile health technologies along with integration of machine learning approaches. The adoption of some novel approaches may not merely replace but could improve existing management strategies and alter common diagnostic paradigms. With these options comes important technical, privacy, ethical, financial, and medicolegal barriers that must be addressed. However, the coronavirus disease 19 pandemic also presents a unique opportunity to augment conventional testing by including innovative and emerging approaches to measuring lung function remotely in patients with respiratory disease. The benefits of such an approach have the potential to enhance respiratory care and empower patient self-management well beyond the current global pandemic.